Generation of CAR-T Cells with Sleeping Beauty Transposon Gene Transfer - Prommersberger, Sabrina; Monjezi, Razieh; Botezatu, Lacramioara; Miskey, Csaba; Amberger, Maximilian; Mestermann, Katrin; Hudecek, Michael; Ivics, Zoltán (Humana Press Inc., 2022)
Human T lymphocytes that transgenically express a chimeric antigen receptor (CAR) have proven efficacy and safety in gene- and cell-based immunotherapy of certain hematological cancers. Appropriate gene vectors and methods of genetic engineering are required for therapeutic cell products to be biologically potent and their manufacturing to be economically viable. Transposon-based gene transfer satisfies these needs, and is currently being evaluated in clinical trials. In this protocol we describe the basic Sleeping Beauty (SB) transposon vector components required for stable gene integration in human cells, with special emphasis on minicircle DNA vectors and the use of synthetic mRNA. We provide a protocol for functional validation of the vector components in cultured human cell lines on the basis of fluorescent reporter gene expression. Finally, we provide a protocol for CAR-T cell engineering and describe assays that address transgene expression, biological potency and genomic vector copy numbers in polyclonal cell populations. Because transposons allow virus-free gene transfer with naked nucleic acids, the protocol can be adopted by any laboratory equipped with biological safety level S1 facilities.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Adoptive cell therapy; Cancer; Chimeric antigen receptor; Gene transfer; Genetic vectors; Genomic integration; Immunotherapy; Transposon; Vector copy number